Cooperation Between Public Research Organizations and the Industry in Slovenia in 2007–2013 - Romana Pogorelec; Stanka Setnikar Cankar (Central European Public Administration Review)
Funding for research and development activities is an important part of every society. In the 2007-2013 period, Slovenia increased the share of gross domestic expenditures for research and development. The share then declined, and Slovenia is again falling short of the set goal of investing three percent of its GDP in research and development. The article presents statistical data on the share of investments in research and development activities in Slovenia in the 2008-2015 period and two measures or instruments introduced in 2009 and 2010 by the Ministry of Higher Education, Science and Technology of the Republic of Slovenia. The stated goal of the measures was to foster collaboration and networking between researchers at public research organizations and the private sector. The measures in question were the Tender for the development of centers of excellence and the Public tender for the development of competency centers in the 2010-2013 period. The measures were co-financed through structural funds.